Study of the Synergistic Effect of Nanoporous Nickel Phosphates on Novel Intumescent Flame Retardant Polypropylene Composites - Shibin Nie; Chi Zhang; Chao Peng; De-yi Wang; Daowei Ding; Qingliang He (Journal of Spectroscopy)
A char forming agent (CFA) and silica-gel microencapsulated ammonium polyphosphate (Si-MCAPP) were selected to form novel intumescent flame retardant system to prepare flame retardant polypropylene (PP) composites, and then the influences of nanoporous nickel phosphates (NiP) on the thermal and flame retardant properties of flame retardant PP composites were studied by the real time FTIR (RTFTIR) spectra, limited oxygen index (LOI) test, and the scanning electron microscopy. RTFTIR shows the addition of NiP can improve the thermal stability of flame retardant PP composites. LOI test shows LOI value is increased with the increase of the content of NiP, and the optimized concentration of NiP is 1.0%. Furthermore, smoke toxicity of the novel flame retardant PP composites was studied by mice experiment. The upper limit of the no death smoke concentration of the composite is 12.37 mg/L.